Be Happy: Navigating Normative Issues in Behavioral and Well-Being Public Policy. (January 2022) - Fabian, Mark; Pykett, Jessica
Psychological science is increasingly influencing public policy. Behavioral public policy (BPP) was a milestone in this regard because it influenced many areas of policy in a general way. Well-being public policy (WPP) is emerging as a second domain of psychological science with general applicability. However, advocacy for WPP is criticized on ethical and political grounds. These criticisms are reminiscent of those directed at BPP over the past decade. This déjà vu suggests the need for interdisciplinary work that establishes normative principles for applying psychological science in public policy. We try to distill such principles for WPP from the normative debates over BPP. We argue that the uptake of BPP by governments was a function of its relatively strong normative and epistemic foundations in libertarian paternalism, or nudging, for short. We explain why the nudge framework is inappropriate for WPP. We then analyze how boosts offer a strict but feasible alternative framework for substantiating the legitimacy of well-being and behavioral policies. We illuminate how some WPPs could be fruitfully promoted as boosts and how they might fall short of the associated criteria.